Numerical investigation of the hydrodynamics of a submersible steel-frame offshore fish farm in regular waves using CFD. (15th July 2022) - Wang, Gang; Martin, Tobias; Huang, Liuyi; Bihs, Hans
Abstract: The hydrodynamics and non-linear interaction between the submersible steel-frame offshore fish farm "ShenLan 1" and regular waves are investigated using the open-source CFD toolbox REEF3D. The effects of the regular wave parameters, different net sheets, and structural variations on the motion responses and mooring forces of the fish farm system are studied. The numerical framework consists of a moored-floating body motion solver for the frame structure coupled to a fluid dynamics solver to simulate the two-phase propagation of the waves. The momentum loss of the flow over fixed net sheets is included in the solver. First, the chosen model is validated for a coupled rigid body motion and net hydrodynamics. Then, the solver is applied to the offshore fish farm "ShenLan 1". It is shown that the surge motions are more sensitive to the wave parameters compared to the heave and pitch motions due to the restrain from the mooring system. In contrast to the vertical components, the horizontal loadings positively correlate with the wave heights and periods. The nets show minor influence on the motion responses, but the percentage of horizontal forces attributed to nets decreases from 55% to 10% in larger wave periods. The translational motions, as well as mooring restoring tensions, are particularly sensitive to shifts of the draught. Finally, the increase of the aspect ratio of "ShenLan 1" through enlarging the overall diameters results in declined motions and mooring forces. Thus, this study provides the first indications towards a systemic evaluation of the dependencies of different structural parts of a submersible steel-frame offshore fish farm for hydrodynamics. Highlights: The effects of the wave parameters and structural variations on the response motions and hydrodynamic loads of the fish farm are studied. An innovative CFD method considering the fluid–structure interactions is adopted. The increase of net solidities shows the minor influence on the response motions of the structure. The non-linear wave structure interactions around the fish farm are resolved.